1977-1978ネン マクマード チイキ チガク チョウサ ホウコク - 矢内, 桂三; ヤナイ, ケイゾウ; 船木, 実; フナキ, ミノル; YANAI, Keizo; FUNAKI, Minoru (国立極地研究所, 1979)
P(論文) 1977-1978年の夏期間,日本から2名がマクマード基地を訪れた.地質調査と古地磁気の試料採集は,日本独自のテーマで,バンダ基地周辺,テーラー谷,ロス島のマクマード基地付近で行った.昨年に続き南極隕石探査は,日米合同で実施し,アランヒルズ周辺の裸氷と雪上で311個の隕石を発見回収した. Two Japanese scientists (authors) visited McMurdo Station and Victoria Land during the 1977-1978 field season. The authors stayed at McMurdo Station from November 16, 1977 to February 2, 1978 for their research. Three research programs were carried out in this season. As a part of comparative study of geological structure in East Antarctica, geological survey of dike rocks was conducted in the Dry Valley area. Many dikes and their mutual relationship were determined in the field near Vanda Station of the Wright Valley and in Taylor Valley. About 200 rock specimens were collected for paleomagnetic studies in the Wright Valley, Taylor Valley, Allan Hills, Carapace Nunatak and Ross Island areas. These specimens consist of the varieties of the basement rocks, many dike rocks in the basement, Beacon Fomation, Ferrar dolerite, and McMurdo volcanic rocks. A U. S.-Japan search for meteorites was conducted again on the basis of the previous season's success. Two U. S. and two Japanese scientists revisited the bare ice field of Allan Hills, Victoria Land, 230 km north of McMurdo Station. During the field season of 1977-1978, the team recovered 311 individual meteorite specimens. departmental bulletin paper